Forms of Touch during Medical Encounters with an Advanced Heart Failure (AdHF) Doctor who Practices Relational Medicine - Raia, Federica; Goodwin, Marjorie H.; Deng, Mario C. (Social Interaction. Video-Based Studies of Human Sociality, 2020)
Within a participatory research project, we investigate how forms of touch we call caring touch are enacted in AdHF medical encounters. Through the theoretical lens of Relational Ontology (Raia, 2018), grounding multimodality in phenomenology, we identify various forms of caring touch. When occurring in conjunction with medical/diagnostic touch, especially in situations of a perceived patient’s vulnerability, caring touch facilitates passages from the person level to the organ, tissue, and gene levels and then back to the whole-person level in an uninterrupted movement, maintaining the person-person relation between doctor and patient. Gentle shepherding (Cekaite, 2010) is used to guide the patient body, and comforting touch (Goodwin & Cekaite, 2018) accompanies invitations to enter a space where death is part of living. We show the existential grounding power of caring touch, which constitutes forms of reciprocal sharing of existential experiences in caring-for-the-Other. All these forms of caring touch are employed by an AdHF doctor whose work centers on the practice of Relational Medicine (Raia and Deng, 2015b), in which the starting and returning point is the patient in his/her life. While providing a single case analysis, the research builds from a corpus of 500 hours of recorded medical encounters with 125 patients in high-tech medicine.